Analysis of factors affecting customer satisfaction in e-commerce applications using Condorcet - AHP method. Issue 1 (2019) - Bhattacharya, Sweta; Raju, V.
The paper proposes a new approach of combining Condorcet voting theory with analytic hierarchy process (AHP) to analyse various criteria affecting customer satisfaction in e-commerce systems. AHP method has been successfully used to resolve MCDM problems in various sectors of human life. But the major weakness of AHP lies in the use of subjective assessment based importance scale point which leads to judgemental errors in results. Condorcet voting and quantitative ratio based method is used to derive the importance of the criteria affecting customer satisfaction eliminating chances of such bias in the traditional AHP technique. The consistency ratio values derived provide support for enhanced accuracy and consistency of the results. The structured analysis of the criteria in this paper thus provide immense insight which would benefit business personnel's to frame strategies pertinent to the most significant criteria impacting customer satisfaction for the overall development of e-commerce systems.